Pengembangan Dan Evaluasi Program Konseling Gizi Intensif Dalam Peningkatan Pengetahuan, Ibu Hamil Terkait Intake Gizi Yang Berkualitas - Daranga, Erniwati; Aminuddin, Aminuddin; Syamsuddin, Saidah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: : the aim of this research is to find out the effect of intensive counselling in improving knowledge of pregnant women related to quality nutrition intake. Methods: the research used Quasi Eksperimen design method wiht pre post control grup one design.the subject consisten of 80 people divided into 2 groups.i.e. 40 people in control group and 40 people in intervention group. the data were processed using kruskal-wallis test to analyze the differences before and after intervention was done in intensive nutrition counselling group andcontrol grupResults: the results of the research that the mean value in intensive group in terms of knowledge is higher than that of control group. Therefore intensive counseling is very effective to inprove respondents knowledgeConclusion: Counseling of Intensive nutrition with using leaflet media can improve knowledge of pregnant women was much better.